2020
DOI: 10.1186/s12894-020-00744-w
|View full text |Cite
|
Sign up to set email alerts
|

532 nm green-light laser vaporization of upper tract urothelial carcinoma

Abstract: Background Endoscopic management of low risk upper tract urothelial carcinoma (UTUC) may be considered in select clinical scenarios, which allows sparing the morbidity of radical nephroureterectomy while achieving acceptable oncological outcomes and preservation of kidney function. Herein, we present a case with UTUC in a solitary kidney managed with 532 nm laser vaporization through a percutaneous approach. Case presentation The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 1 Laser ablation remains the most dominant method among the kinds of endoscopic techniques applied so far. 1 , 10 These therapeutic options should also be considered for selected patients, for example, those with a solitary kidney, bilateral UTUC, and renal insufficiency, even in high-risk cases. It is regrettable that patients with high-grade disease often fare poorly in consideration of existing modalities.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Laser ablation remains the most dominant method among the kinds of endoscopic techniques applied so far. 1 , 10 These therapeutic options should also be considered for selected patients, for example, those with a solitary kidney, bilateral UTUC, and renal insufficiency, even in high-risk cases. It is regrettable that patients with high-grade disease often fare poorly in consideration of existing modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo trials have shown deep coagulation and high vaporization effects at high-power settings [ 37 ]. These characteristics may make them candidates for vaporization of UTUC, but the significant coagulation depth of the Greenlight laser limits its usability for UTUC treatment, resulting in limited evidence regarding its efficiency [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the deep tissue effects of diode lasers and Nd:YAG theoretically might cause ureteral perforation and thus have to be applied carefully for the endoscopic treatment of UTUC. The experience of diode laser (T-1470 LiteTouch™) use for UTUC treatment is described mostly in case reports with promising reports regarding perioperative outcomes [ 38 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, different kinds of lasers have been utilised in the treatment of UTUC, such as the 532-nm KTP laser, thulium laser (Tm:YAG) and holmium laser (Ho:YAG) [ 6 , 12 14 ]. The purpose of various laser studies and applications was to explore its feasibility, safety and effectiveness.…”
Section: Discussionmentioning
confidence: 99%